GREEN MARKETING INNOVATION AS MSME's COMPETITIVE ENHANCEMENT STRATEGY IN PEMATANG SERAI VILLAGE - Sanny, Annisa; Daulay, Muhammad Toyib; Ritonga, Husni Muharam; Putri, Indry Febrianti (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Green Marketing is defined as a marketing strategy that emphasizes environmental and sustainability aspects in products, promotions, and business practices. Pematang Serai Village was chosen as the research location because it is an area with MSME potential involving the local economic sector and the natural environment. Through a field researsch approach involving 50 MSME business with various types of businesses in Pematang Serai Village. The results showed that the implementation of Green Marketing had a positive impact on the competitiveness of MSMEs in Pematang Serai Village. MSMEs that implement sustainable marketing practices can differentiate themselves, attract environmentally conscious consumers, and gain a competitive advantage. Supporting factors include awareness of MSME owners about sustainable practices, government support, and access to resources and information that support Green Marketing. Barriers include limited resources, limited understanding of Green Marketing, and challenges in changing consumer behavior. This research is important to expand the understanding of the implementation of Green Marketing in MSMEs in rural areas. The implication is the importance of government and stakeholder support in facilitating sustainable MSME development and encouraging the adoption of environmentally friendly marketing practices